Defect characterisation of tensile loaded CFRP and GFRP laminates used in energy applications by means of infrared thermography. Issue 1 (2nd January 2018) - Maierhofer, Christiane; Krankenhagen, Rainer; Röllig, Mathias; Rehmer, Birgit; Gower, Mike; Baker, Graham; Lodeiro, Maria; Aktas, Alper; Monte, Christian; Adibekyan, Albert; Gutschwager, Bernd
Abstract: The increased use of fibre reinforced plastic (FRP) composites for improved efficiency and reliability in energy related applications, e.g. wind and marine turbine blades, nacelles, oil and gas flexible risers, also increases the demand for innovative non-destructive testing technologies. In this contribution, results concerning the characterisation of CFRP and GFRP during and after quasi-static tensile loading are presented. It includes the measurement of optical properties in the infrared spectral range, tensile loading tests with the observation of the temperature distribution at one or both sides of the specimens using an infrared camera for the preparation and monitoring of intended natural defects, and active thermography inspections after tensile loading. It is shown that the defect preparation was successful. Thermographic monitoring during and active thermography testing after tensile loading enable the detection of the lateral extend of the generated defects. Differences between CFRP and GFRP materials are discussed.